PELATIHAN PEMBUATAN BIJI KOPI FERMENTASI UNTUK KELOMPOK REPUBLIK TANI MANDIRI DESA KUCUR MALANG (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Coffee has a very big role in increasing the country's foreign exchange. Coffee production has increased drastically throughout Indonesia. One of the coffee-producing areas is Kucur Village. Kucur Village is located in the highlands of Malang Regency which produces Robusta, Arabica, and Liberica coffee varieties. Republik Tani Mandiri (RTM) is a farmer group that sells coffee. However, the coffee product produced is still in the form of ground coffee and innovations need to be added to increase the selling value of coffee. The community service team of Ma Chung University provides training for the manufacture of fermented coffee in the hope that the selling price of coffee can increase. The coffee bean fermentation process uses the Saccharomyces cerevise fungus, the fermentation temperature is 30℃, and the fermentation time is 30 days. The results of this training show that the training process is good and partners consider that this activity should be continued until the packaging process